2020
DOI: 10.3390/w12030880
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of Soil Salinization in an Arid Region of the Keriya Oasis Based on Multidimensional Modeling

Abstract: Soil salinity is one of the major factors causing land degradation and desertification on earth, especially its important damage to farming activities and land-use management in arid and semiarid regions. The salt-affected land is predominant in the Keriya River area of Northwestern China. Then, there is an urgent need for rapid, accurate, and economical monitoring in the salt-affected land. In this study, we used the electrical conductivity (EC) of 353 ground-truth measurements and predictive capability param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In some other studies, it was also concluded that optimized spectral indices combined with spectral transformation could achieve better modeling results and had good inversion feasibility [30,31]. Nijat et al used the multi-dimensional modeling method to quantitatively retrieve the SSC on the basis of the WorldView-2 multi-spectral imagery [32], and the results obtained were consistent with the views of Li. that the ANN model was a powerful tool for inversion of SOC in farmland areas [7].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…In some other studies, it was also concluded that optimized spectral indices combined with spectral transformation could achieve better modeling results and had good inversion feasibility [30,31]. Nijat et al used the multi-dimensional modeling method to quantitatively retrieve the SSC on the basis of the WorldView-2 multi-spectral imagery [32], and the results obtained were consistent with the views of Li. that the ANN model was a powerful tool for inversion of SOC in farmland areas [7].…”
Section: Introductionmentioning
confidence: 81%
“…Partial least squares (PLS) is a mathematical optimization technique that finds the best function match for a set of data by minimizing the sum of squares of errors [32]. PLSR ≈ MLR + canonical correlation analysis (CCA) + principal component analysis (PCA).…”
Section: (4) Plsr Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The main goal of this Special Issue of Water is to focus on different methodological approaches to improve the understanding of salinization mechanisms of both groundwater and soil water, which may derive from actual seawater intrusion, paleo-seawater intrusion, an increase in atmospheric temperatures that in turn drives evapoconcentration and agricultural return flows. From its first announcement, and after being thoroughly peer reviewed, six papers have been accepted for publication [10][11][12][13][14][15]. To gain an overview of the ideas collected by this Special Issue, a brief summary of each published paper is reported below.…”
Section: Contributionsmentioning
confidence: 99%
“…Another contribution of this Special Issue tackles complex transboundary aquifer management affected by different sources of salinization that threaten the well field of the Lower Yarmouk Gorge (LYG) shared by Israel, Jordan and Syria [13]. In a different line of research, the study presented by Kasim et al [14] analyzed the salt-affected land which is predominant in the Keriya River area of Northwestern China via satellite band reflectance and newly optimum spectral indices (OSIs) based on two-dimensional and three-dimensional data. Finally, a review paper closes this Special Issue discussing the new advances and challenges that still must be faced in the Mediterranean with a special focus on predictions of climate change effects on coastal aquifers, which surely deserve additional research [15].…”
Section: Contributionsmentioning
confidence: 99%